Trademark rights, comparative advertising, and "perfume comparison lists": An untold story of law and economics - Tim W. Dornis; Thomas Wein (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
Regarding trademarks, the EU and US regulate comparative advertising differently. One particular matter of significant difference is whether or not competitors are allowed to say they offer an imitation or replica of a trademarked product. In the US, competitors may claim equality of their product as long they clearly eliminate confusion and distinctly market their product as separate from the original. European firms, by contrast, face more obstacles concerning advertising statements conceived to establish their product as equal or identical to a competitor's trademarked product. If the economic functions of trademarks are clear, it is easier to answer a number of legal questions in the comparative advertising field. One facet rarely explored is the fact that trademarks are the “name” of a product and the legal bridge between consumers' past and future experiences. Such experiences are referred to as attributes or qualities of a product. Attributes describe product characteristics driving individual consumer experiences. Because such experiences are difficult to objectively verify, statements of this kind must submit to particular scrutiny. In principle, the same is true regarding product qualities. Quite often, it is easy to measure quality experiences, but sometimes measuring is not possible depending on whether qualities are public or private. Like with attributes, the legality of referring to product qualities depends on verifiability. Uncertainty of an attribute's verifiability or quality information creates a risk of undue exploitation, particularly consumer confusion. In such cases, strict regulation of comparative advertising is important. In other words, the legal system must prevent confusion in advertising because confusion increases consumer search costs. In addition to preventing confusion, the issue of trademark dilution is another aspect relevant in analyzing comparative advertising. According to European doctrine, using a competitor's trademark in comparative advertising can be improper goodwill misappropriation. Displaying a competitor's trademark may diminish its distinctiveness, tarnish its image and reputation, or constitute what the ECJ defines as freeriding or parasitic competition. The meandering standards of legal doctrine, however, hardly provide for consistent guidelines. Whether misappropriation is a justifiable term to use in defining comparative advertising requires a closer look at the field's underlying economics. As we will show, in none of these constellations will the appropriation of the competitor's investment be implemented through the market mechanism. It is not a pecuniary, but a technological externality. The metric for assessing admissibility of appropriation must thus be changed from the governing European doctrine of necessity or proportionality to a principle of economic efficiency taking into account both the trademark owner's and the advertising competitor's cost-benefit-ratio.
Keywords: 330